EFEKTIFITAS KATALIS Co/Mo PADA HYDROCRACKING MINYAK NYAMPLUNG - Rismawati - Rasyid; Ricco Aditya S. W; Devita Dian.L; Mahfud Mahfud; Achmad Roesyadi (Dept. of Chemical Engineering, Diponegoro University, 2015)
THE EFFECTIVTY OF Co/Mo CATALYSTS IN HYDROCRACKING OF NYAMPLUNG OIL. Hydrocracking process of Nyamplung Oil was presented using Co and Mo as metal catalysts. Ratio of CoMo metals in catalysts, can give better catalytic activity for Nyamplung Oil conversion. In this process, we used Co/Mo ratio (0.264/0.64), (0.62/1.61), and (1.23/3.22) towards SiO2 dan γ-Al2O3. This catalyst has made by wet impregnation method with drying temperature at 383 K during 8 hours and was calcined at 773 K for 5 hours. This catalyst was characterized by X-Ray Diffraction (XRD) and showed Co3O4, MoO3 and CoMoO4 substances that was deposited at CoMo/SiO2 catalyst surface. Then, Co3O4, MoO3, MoO2 and CoMoO4 substances was also appeared at CoMo/γ-Al2O3 catalyst surface. That all phases which is deposited at both of this catalyst surface, is appropriate with International Centre for Diffraction Data (ICDD standards). Then, this catalyst was used for hydrocracking process of Nyamplung Oil that takes place at batch reactor. That process was carried out at 3 MPa and 623 K over 2 hours. C5-C11 dan C12-C18 products was produced from Nyamplung Oil conversion using this process. Both of this products is increased correspond to the addition of Co and Mo metals ratio. The highest yield that was achieved is C5-C11 (24.30%) and C12-C18 (61.28%) when using Co/Mo (1.23/3.22)/γ-Al2O3 catalyst. Meanwhile, Co/Mo (1.23/3.22)/ SiO2 catalyst can produce C5-C11 (19.52%) and C12-C18 (53.55%). Keywords: CoMo catalyst; hydrocracking; nyamplung oil Abstrak Rasio katalis CoMo sebagai katalis logam memiliki aktivitas yang baik dalam mengkonversi minyak nyamplung. Proses hydrocracking menggunakan rasio Co/Mo (0,24/0,64), (0,62/1,61), dan (1,23/3,22) terhadap SiO2 dan γ-Al2O3. Katalis tersebut menggunakan metode impregnasi basah dengan suhu pengeringan 383 K selama 8 jam dan dikalsinasi selama 5 jam pada suhu 773 K. Karakterisasi katalis menggunakan XRD (X-ray diffraction) menunjukkan komponen Co3O4, MoO3 dan CoMoO4 terdeposisi pada permukaan katalis CoMo/SiO2. Kemudian untuk katalis CoMo/γ-Al2O3 terdapat Co3O4, MoO3, MoO2 dan CoMoO4 dipermukaan katalis. Fase yang terdeposisi pada permukaan kedua katalis disesuaikan dengan standar ICCD (International Centre for Diffraction Data). Hasil uji aktivitas katalis tersebut menggunakan reaktor batch dengan tekanan 3 MP dan temperatur 623 K, proses reaksi dilakukan selama 120 menit. Konversi minyak nyamplung ada proses hydrocracking diperoleh produk C5-C11 dan C12-C18. Persentase yield kedua jenis produk meningkat sesuai dengan penambahan rasio Co dan Mo. Produk dengan yield tertinggi pada katalis Co/Mo (1,23/3,22)/ SiO2 dengan C5-C11 (19,52%) dan C12-C18 (53,55%). Sementara untuk katalis Co/Mo (1,23/3,22)/ γ-Al2O3 diperoleh C5-C11 (24,30%) dan C12-C18 (61,28%). Kata kunci: katalis CoMo; hydrocracking; minyak nyamplung